Suffering in children and adolescents in paediatric palliative care in Spain: psychometric properties of the qESNA scale - Daniel Toro-Pérez; Joaquin T. Limonero; Catalina Bolancé; Montserrat Guillen; Sergi Navarro-Vilarrubí; Ester Camprodon-Rosanas (Elsevier, 2024)
Objective: To analyze the psychometric properties of the qESNA scale and its usefulness to assess the suffering of paediatric patients with life-limiting and/or life-threatening diseases (children with LLTC) in clinical practice. Methods: Cross-sectional and longitudinal study in 58 patients in Spain (female, 32.8%; mean age, 15.6 [SD, 4.5]; age range, 8-23 years), with administration of the qESNA scale along with other scales to assess anxiety, depression, emotion regulation and psychosocial functioning. We performed exploratory and confirmatory factor analyses and calculated goodness-of-fit indices were calculated; we assessed reliability by means of the Cronbach alpha and temporal stability and convergent validity through the intraclass correlation coefficient with scales used to assess psychological disorders and the specificity and sensitivity through ROC curves. Results: The factor analysis identified a 14-item scale with 3 factors, a comparative fit index of 0.93, a Tucker-Lewis index of 0.91 and a root mean square error of approximation of 0.07. The Cronbach alpha was 0.85 and the intraclass correlation coefficient was 0.66. The convergent validity was high for the correlation to the risk of depression (−0.69) and of anxiety (−0.60) and emotional changes (−0.59). The analysis of the ROC curves showed that a score of less than 81 would be indicative of suffering, with a sensitivity of 83.33% and a specificity of 93.48%. Conclusions: This study confirmed that the psychometric properties of the qESNA scale are good and the scale's usefulness as an instrument to detect emotional suffering in children with life-limiting or life-threatening illnesses in clinical practice. Resumen: Objetivo: Analizar las propiedades psicométricas de la escala qESNA y su utilidad clínica para evaluar el sufrimiento de pacientes infantojuveniles con enfermedades limitantes y/o amenazantes para la vida (niños con LLTC). Métodos: 58 pacientes en población española (mujeres = 32.8%; edad media = 15.6 ± 4.5 [8-23 años]), respondieron a la escala qESNA en un diseño transversal y longitudinal junto con otras escalas que evaluaban ansiedad, depresión, alteraciones emocionales y funcionamiento psicosocial. Se realizaron análisis factoriales exploratorios y confirmatorios, y calcularon índices de bondad de ajuste; la fiabilidad se obtuvo a partir del alfa de Cronbach y de estabilidad temporal; la validez convergente mediante coeficientes de correlación intraclase con escalas sobre alteraciones psicológicas; y el análisis de especificidad y sensibilidad a través de las curvas ROC. Resultados: El análisis factorial identificó una escala de 14 ítems con 3 factores, con un índice de ajuste comparativo de 0.93, índice de Tucker-Lewis de 0.91 y error cuadrático medio de aproximación de 0.07. El alfa de Cronbach fue de 0.85 y el coeficiente correlación intraclases de 0.66. La validez convergente fue alta en la correlación con el riesgo de depresión (-0.69) y ansiedad de (-0.60) y las alteraciones emocionales (-0.59). Los análisis de curvas ROC indican que una puntuación <81 sería tributaria de sufrimiento presentando una sensibilidad del 83.33% y especificidad de 93.48%. Conclusiones: Este estudio confirma las buenas propiedades psicométricas de la escala qESNA y su utilidad clínica como instrumento para detectar el sufrimiento emocional en niños con enfermedades limitantes o amenazantes para la vida.